Effect of Transversus Abdominis Plane Block with Dexmedetomidine and Clonidine on Numerical Rating Scale and Interleukin–6 - Heryadi, Mohamad Ismu; Purnomo, Heri Dwi; Arianto, Ardana Tri (Jurnal Anestesi Perioperatif, 2026)
Background: The use of adjuvants like dexmedetomidine and clonidine in Tranversus Abdominis Plane (TAP) blocks can enhance analgesic effects. This study aimed to compare the impact of these adjuvants on TAP blocks by measuring postoperative pain using the numerical rating scale (NRS) and interleukin-6 (IL-6) levels.Methods: This study was conducted from January to April 2024 at the Central Surgical Installation of Dr. Moewardi using a double-masked randomized controlled trial design. The study involved 30 patients undergoing cesarean section, divided into two groups: Group A (15 received a TAP block with dexmedetomidine 0.5 mcg/kgBB) and Group B (15 received a TAP block with clonidine 0.5 mcg/kgBB).Results: Independent tests revealed significant differences in NRS and IL-6 levels between the groups (p<0.001), indicating that dexmedetomidine is superior at preventing NRS and IL-6 elevation.Discussion: Conventional epidural opioids effectively manage pain but cause significant side effects and serious risks, including delayed respiratory depression in mothers and adverse effects on breastfed infants, necessitating alternative approaches. TAP block with dexmedetomidine and clonidine adjuvants demonstrated significant effectiveness in reducing postoperative pain, with dexmedetomidine proving superior in prolonging analgesia duration, decreasing rescue medication requirements, and reducing opioid consumption through its anti-inflammatory effects.Conclusion: These findings highlight the positive effects of dexmedetomidine in reducing postoperative inflammation and pain. The results provide grounds for considering dexmedetomidine as an adjuvant in TAP blocks to enhance effective postoperative pain management.